OW DIFFERENT ARE THE PERCEPTIONS OVER THE MAIN MOTIVATIONAL TOOLS IN MILITARY? AN ANALYTIC HIERARCHY PROCESS (AHP) APPROACH. - Paul - Mugurel POLEANSCHI (Journal of Defense Resources Management, 2014)
In the Romanian military system, motivational rewards based on merits are precisely regulated and ranked as confined by the military order in which they are mentioned. The existing hierarchy of these main motivational rewards is partly inherited, partly harmonized with other international military partner organizations and it is implicitly assumed that decision makers are able to equidistantly evaluate the merits of their subordinates. Still, decision makers’ personal, implicit perceptions over the importance and the effectiveness of the available rewards designed to enhance motivation among their subordinates can alter for good or for worse the efficiency of these motivational tools. This paper aims at quantifying the implicit perceptions of the decision makers in a military organization over four main motivational tools through the construction of a hierarchy based on an analytic hierarchy process approach whose final alternatives are constituted by the four motivational tools. A survey asking for pair wise comparison among criteria, sub criteria and alternatives, completed by the use of two numerical scale alternatives, led to priority vectors assessing the relative importance of the rewards considered. The findings on the perceived importance of the rewards might lead to further research, with a potential discussion on the design of the motivational tools or on a different approach to distributing the existent ones.